Population-adjusted indirect treatment comparison of maintenance PARP inhibitor with or without bevacizumab versus bevacizumab alone in women with newly diagnosed advanced ovarian cancer. (September 2021) - Hettle, Robert; McCrea, Charles; Lee, Chee Khoon; Davidson, Richard
Background: In patients with newly diagnosed ovarian cancer, bevacizumab and poly(ADP-ribose) polymerase (PARP) inhibitors, alone or in combination, have shown benefit as maintenance treatment following platinum-based chemotherapy. However, no trials have compared a PARP inhibitor plus bevacizumab versus a PARP inhibitor, or a PARP inhibitor versus bevacizumab. We performed an unanchored population-adjusted indirect treatment comparison to estimate the relative efficacy and safety of maintenance treatments for newly diagnosed advanced ovarian cancer. Methods: Analyses were performed using aggregate data from the PRIMA trial and patient-level data from a subset of patients from the PAOLA-1 trial that met surgery and staging eligibility criteria of PRIMA. Propensity weights were used to match baseline characteristics of the PAOLA-1 subset to those of the PRIMA population. Analysis was performed in overall (biomarker-unselected) and homologous recombination repair deficiency (HRD)-positive populations. Results: A total of 595/806 (266/387 HRD-positive) PAOLA-1 patients were included. After matching, the effective sample size for PAOLA-1 was 532 (242 HRD-positive). Maintenance olaparib plus bevacizumab reduced the risk of disease progression or death by 43% [hazard ratio (HR) 0.57; 95% confidence interval (CI): 0.47–0.69] versus niraparib and by 40% (HR 0.60; 95% CI: 0.49–0.74) versus bevacizumab in the biomarker-unselected population and by 43% (HR 0.57; 95% CI: 0.41–0.79) and 60% (HR 0.40; 95% CI: 0.29–0.55), respectively, in the HRD-positive population. Progression-free survival (PFS) benefits of maintenance niraparib and bevacizumab arms were comparable in the biomarker-unselected population (HR 1.07; 95% CI: 0.87–1.32); however, niraparib showed a 30% reduced risk compared with bevacizumab (HR 0.70; 95% CI: 0.51–0.97) in the HRD-positive population. Conclusions: In biomarker-unselected and HRD-positive patients, combination treatment with olaparib plus bevacizumab as maintenance treatment improves PFS for women with newly diagnosed advanced ovarian cancer compared with either bevacizumab or niraparib alone. Results are hypothesis generating and could guide randomised trial design.